Mitochondrial DNA variation in wild populations of Leporinus elongatus from the Paraná River basin - Martins, Cesar [UNESP]; Wasko, Adriane Pinto [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Sociedade Brasileira de Genética, 2003)
Leporinus elongatus, a fish species widely distributed throughout the Paraná River basin in South America, is an important fishery resource and a valuable species in aquaculture programs. Despite its great economic importance, several wild populations have been suffering a drastic reduction. The comprehension of its population structure represents an important step for the conservation of these organisms in natural environments, and also for the selection of wild stocks to be used in hatchery programs. In order to understand the genetic-population structure of L. elongatus, D-loop mitochondrial DNA analyses were applied in six wild populations of the species. The results were used to estimate the levels of within and among population genetic variability. Although the D-loop variations could not be correlated to the geographic distribution of these organisms, it was possible to detect high levels of genetic variability within each population and the occurrence of exclusive population haplotypes, which suggests a partial genetic differentiation among them. The obtained data can be useful in selecting fish stocks that preserve a better genetic diversity of L. elongatus for use in conservation and/or hatchery programs.
Keywords: conservation genetics; D-loop; genetic variability; Leporinus elongatus; mtDNA